2013
DOI: 10.1144/jgs2012-037
|View full text |Cite
|
Sign up to set email alerts
|

Large sulphur isotopic perturbations and oceanic changes during the Frasnian–Famennian transition of the Late Devonian

Abstract: The Frasnian-Famennian transition of the Late Devonian was one of the most critical intervals in the Phanerozoic. Sulphur isotopic pairs of carbonate-associated sulphate and pyrite sulphide from coeval sections in South China and Poland reveal frequent perturbations of sulphur cycling during this time interval. These data suggest a sudden oceanic overturn during a rapid sea-level fall probably induced by jerky block tilting in the latest Frasnian. This event was followed by long-lasting photic-zone euxinia dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
44
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 67 publications
6
44
2
Order By: Relevance
“…3). Similar δ 34 S values were previously reported in some European Late Devonian sediments (Joachimski et al, 2001) although sediments from Northern America, Southern China and Poland from the same time period showed more positive values (Goodfellow and Jonasson, 1984;Chen et al, 2013). Table 1 Selected elemental and molecular maturity parameters throughout the MR-1 core indicating an exceptionally low thermal maturity.…”
Section: δ 34 S Of Pyritesupporting
confidence: 81%
“…3). Similar δ 34 S values were previously reported in some European Late Devonian sediments (Joachimski et al, 2001) although sediments from Northern America, Southern China and Poland from the same time period showed more positive values (Goodfellow and Jonasson, 1984;Chen et al, 2013). Table 1 Selected elemental and molecular maturity parameters throughout the MR-1 core indicating an exceptionally low thermal maturity.…”
Section: δ 34 S Of Pyritesupporting
confidence: 81%
“…Geochemistry, sedimentology, and other faunal evidence (e.g. conodonts) suggest a slope environment in the Yangdi section (Ji, 1989;Ma and Bai, 2002;Chen et al, 2013;Huang and Gong, 2016). However, none of the spinose podocopids (indicative of deep-and cold-water environments; Blumenstengel, 1965Blumenstengel, , 1979Kozur, 1972;Bandel and Becker, 1975;Lethiers and Crasquin, 1987;Wang, 1988;Casier, 2004; some authors also considered spinose-podocopid ostracod assemblages as indicative for low-energy environments, which might not be particularly deep or cold; Becker, 2000;Groos-Uffenorde et al, 2000) were found together with the smooth-podocopid association in the Yangdi section.…”
Section: Palaeoenvironmental Analysismentioning
confidence: 99%
“…It is a well-outcropped section with continuous deposition of the Late Devonian, which has been studied in detail for biostratigraphy, lithostratigraphy, chemostratigraphy and cyclostratigraphy (Ji, 1989;Gong et al, 1997Gong et al, , 2005Wang, 1990;Ma and Bai, 2002;Chen et al, 2013). A reliable and high-resolution conodont biostratigraphy has been established in this section by Huang and Gong (2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two high-resolution studies that utilized carbonateassociated sulfate to reconstruct the sulfur isotope composition of seawater sulfate have reported negative excursions in δ 34 S SO 4 near the F-F boundary (John et al, 2010;Chen et al, 2013). This negative excursion δ 34 S is potentially reflected in our δ 34 S py data from the Lower Antrim at the LKE and UKE.…”
Section: Euxinia and The Frasnian-famennian Marine S-isotope Recordmentioning
confidence: 71%
“…However, such a mechanism leading to the synchronous and uniform distribution of this sulfate to the ocean, while also delivering enough material to impact the δ 34 S SO 4 , is difficult to rectify on a global scale. Alternatively, Chen et al (2013) advocated that the transient decline in δ 34 S SO 4 was caused by both the increased delivery of continentally weathered sulfur and the oxidation of sulfide from euxinic water masses in epicontinental water columns. In basins that turn euxinic, iron becomes the limiting reagent in the formation of pyrite leading to accumulation of aqueous sulfide.…”
Section: Euxinia and The Frasnian-famennian Marine S-isotope Recordmentioning
confidence: 99%